IMPLEMENTASI RESTORATIVE JUSTICE TINDAK PIDANA RINGAN SEBAGAI SOLUSI MENGURANGI OVERCROWDING LEMBAGA PEMASYARAKATAN DI JAWA TENGAH - Febriansyah, Yoga; Utomo, Eko Fitra; Frans, Mardian Putra (The Juris, 2024)
This research aims to find out and analyze whether the application of restorative justice in relation to criminal acts of theft in society has been able to effectively reduce overcrowding in Central Java? The fact in correctional institutions is that there is overcrowding or it could be said that there are too many prisoners occupying one cell in a correctional institution. Problems like this can cause discomfort in correctional institutions for prisoners which can affect the mental and physical health of prisoners who live in cells that do not match capacity. which is there to be inhabited or what is known as overcrowding, then one way to reduce overcrowding is with restorative justice, namely so that minor crimes such as theft and others can be resolved amicably and not escalated in order to reduce the accumulation of prisoners which causes overcrowding in correctional institutions in the region. Central Java, By using empirical legal methodology, it is hoped that this research can find out whether the application of restorative justice in society for minor crimes can reduce overcrowding in correctional institutions in Central Java.